Data on broad bean beetle (Bruchus rufimanus) damage, bumblebee pollination (Bombus terrestris) and faba bean (Vicia faba) yield - cage experiment in Sweden - Riggi, Laura (Swedish University of Agricultural Sciences, 2022)
Identifying and quantifying crop stressors interactions in agroecosystems is necessary to guide sustainable crop management strategies. Over the last 50 years, faba bean cropping area has been declining, partly due to yield instabilities associated to uneven insect pollination and herbivory. Yet, the effect of interactions between pollinators and a key pest, the broad bean beetle Bruchus rufimanus (florivorous and seed predating herbivore) on faba bean yield has not been investigated.

Using a factorial cage experiment (2 x 2 m) in the field we investigated how interactions between insect pollination by bumblebees and herbivory by the broad bean beetle, affect faba bean yield.
The data on pest damage , pollinators visitation and behavior and faba bean yield components and biomass used in the paper:
Riggi, L., Raderschall, C., & Lundin, O. (2022). Insect pest damage increases faba bean (Vicia faba) yield components but only in the absence of insect pollination. In Ecology and Evolution (Vol. 12). https://doi.org/10.1002/ece3.8686
is presented.

The data material on pest, pest damage, pollinators visitation and faba bean yield components used in the paper:
Riggi, L., Raderschall, C., & Lundin, O. (2022). Insect pest damage increases faba bean (Vicia faba) yield components but only in the absence of insect pollination. In Ecology and Evolution (Vol. 12). https://doi.org/10.1002/ece3.8686

Att identifiera och kvantifiera interaktioner mellan stressfaktorer som påverkar grödor i agroekosystem är nödvändigt för att guida hållbara grödskötselstrategier. Under de senaste 50 åren har arealen med åkerbönor minskat, delvis på grund av instabila skördar kopplade till ojämn pollinering och herbivori. Effekterna av interaktioner mellan pollinerare och en viktig skadegörare, bönsmyg Bruchus rufimanus (blom- och fröätande herbivor) på åkerbönsskörden har dock inte undersökts. Med hjälp av ett faktoriellt burförsök undersökte vi hur interaktioner mellan förmodade två stressfaktorer, avsaknad av insektspollinering och herbivori orsakad av bönsmyg, påverkar åkerbönsskörden. Data om skadegörare, pollinerare och åkerbönsskördekomponeter använda i publikationen:
Riggi, L., Raderschall, C., & Lundin, O. (2022). Insect pest damage increases faba bean (Vicia faba) yield components but only in the absence of insect pollination. In Ecology and Evolution (Vol. 12). https://doi.org/10.1002/ece3.8686
presenteras.

Data om skadegörare, pollinerare och åkerbönsskördekomponeter som använda i publikationen:
Riggi, L., Raderschall, C., & Lundin, O. (2022). Insect pest damage increases faba bean (Vicia faba) yield components but only in the absence of insect pollination. In Ecology and Evolution (Vol. 12). https://doi.org/10.1002/ece3.8686
Data om skador på bondbönor (Bruchus rufimanus), pollinering av humle (Bombus terrestris) och skörd av fababöna (Vicia faba) - burförsök i Sverige
Keywords: Ecosystem services; Ekosystemtjänster; Ecology; Ekologi; Agricultural Science; Jordbruksvetenskap